Upaya Pencegahan Dan Penanganan Tindak Pidana Penyalahgunaan Narkoba Oleh Anak Di Bawah Umur - Daniel R Sihite; Stefy Margaretha; Reh Bungana Beru PA; Maulana Ibrahim (Universitas Sains dan Teknologi Komputer, 2024)
This article discusses efforts to prevent and handle criminal acts of drug abuse by minors. Drug abuse is no stranger to society, but it has also become a culture in this country. This is due to the belief that consuming drugs will reduce the problem so that the spread of drugs is increasingly rapid at this time. So here we need to discuss what efforts can be made to deal with drug abuse and efforts to prevent drug abuse. The method used in this writing uses research methods using library materials or secondary data. The research specifications used are analytical descriptive. Descriptive research is intended to describe the policies that apply to efforts to prevent and handle drugs by minors.